IMPACT OF HAND-TO-HAND COMBAT READINESS ON SENSOMOTOR REACTION AND COGNITIVE DECISION-MAKING RATE (Proximus Journal of Sports Science and Physical Education, 2026)
This scientific study is devoted to the study of the impact of hand-to-hand combat readiness on sensomotor reaction rates as well as cognitive decision-making processes. During the study, experimental and control groups were formed, in which, with the help of special tests, indicators of reaction and decision-making were evaluated. In particular, cognitive processes have been analyzed through simple and selective reaction time, as well as Stroop and Go/No-Go tests